Contemporary Indigenous cosmologies and pragmatics - Dussart, Françoise; Poirier, Sylvie (University of Alberta Press, 2021)
"In this timely collection, the authors examine Indigenous peoples' negotiations with different cosmologies in a globalized world. Dussart and Poirier outline a sophisticated theory of change that accounts for the complexity of Indigenous peoples' engagement with Christianity and other cosmologies, their own colonial experiences, as well as their ongoing relationships to place and kin. Contributors to this volume offer fine-grained ethnographic studies that highlight the complex and pragmatic ways in which Indigenous peoples enact their cosmologies and articulate their identity as forms of affirmation. This collection is a major contribution to the anthropology of religion, religious studies, and Indigenous studies worldwide. Contributors: Anne-Marie Colpron, Robert R. Crépeau, Françoise Dussart, Ingrid Hall, Laurent Jérôme, Frédéric Laugrand, James MacKenzie, Caroline Nepton Hotte, Ksenia Pimenova, Sylvie Poirier, Kathryn Rountree, Antonella Tassinari, Petronella Vaarzon-Morel."--